Instant dynamic response measurements for crack monitoring in metallic beams - Zai, Behzad Ahmed; Khan, Muhammad A.; Mansoor, Asif; Khan, Sohaib Z.; Khan, Kamran Ahmed (British Institute of Non-destructive Testing, 2019)
This paper investigates the interdependencies of the modal behaviour of a cantilever beam, its dynamic response and crack growth. A methodology is proposed that can predict crack growth in a metallic beam using only its dynamic response. Analytical and numerical relationships are formulated between the fundamental mode and crack growth using the existing literature and finite element analysis (FEA) software, respectively. A relationship between the dynamic response and the modal behaviour is formulated empirically. All three relationships are used to predict crack growth and propagation. The load conditions are considered the same in all of the experiments for both model development and model validation. The predicted crack growth is compared with the visual observations. The overall error is within acceptable limits in all comparisons. The results obtained demonstrate the possibility of diagnosing crack growth in metallic beams at any instant within the operational conditions and environment.
Keywords: Catastrophic failure; Mathematical models; Modal behaviour; Crack growth; Dynamic response